2017
DOI: 10.1021/acs.nanolett.6b04638
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Structural Reconstructions, Electronic Properties, and Magnetic Orderings along Different Edges of Zigzag Transition Metal Dichalcogenide Nanoribbons

Abstract: Two-dimensional transition metal dichalcogenides represent an emerging class of layered materials exhibiting various intriguing properties, and integration of such materials for potential device applications will necessarily invoke further reduction of their dimensionality. Using first-principles approaches, here we investigate the structural, electronic, and magnetic properties along the two different edges of zigzag MX (M = Mo, W; X = S, Se) nanoribbons. Along the M edges, we reveal a previously unrecognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
86
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 36 publications
10
86
0
5
Order By: Relevance
“…This explains why in Fig. 3c, the electronic structures of the edges expand over 3 nm (spectra #4–#11 and #22–#31), much wider than the calculated ones33. We have used different tips and found that the width of this extended edge region varies, confirming that this extended edge width is due to the probe shape.…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…This explains why in Fig. 3c, the electronic structures of the edges expand over 3 nm (spectra #4–#11 and #22–#31), much wider than the calculated ones33. We have used different tips and found that the width of this extended edge region varies, confirming that this extended edge width is due to the probe shape.…”
Section: Resultsmentioning
confidence: 51%
“…At this point it is worthwhile to note that, almost all experimental results, including the STS data in the present study, show a finite bandgap at the edge46; in contrast, most theoretical calculations would predict a metallic3233 edge. Such an inconsistency might be due to the lacking of accurate atomic models of the zigzag edges.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations